2002
DOI: 10.1001/jama.287.17.2236
|View full text |Cite|
|
Sign up to set email alerts
|

Anthrax as a Biological Weapon, 2002

Abstract: Specific recommendations include diagnosis of anthrax infection, indications for vaccination, therapy, postexposure prophylaxis, decontamination of the environment, and suggested research. This revised consensus statement presents new information based on the analysis of the anthrax attacks of 2001, including developments in the investigation of the anthrax attacks of 2001; important symptoms, signs, and laboratory studies; new diagnostic clues that may help future recognition of this disease; current anthrax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
316
0
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 923 publications
(325 citation statements)
references
References 71 publications
(107 reference statements)
1
316
0
8
Order By: Relevance
“…Finally, massive edema and organ failure are produced as a consequence of toxin formation. Experience with the 2001 bioterrorism incident found that, once the disease reaches the phase during which patients show evidence of significant toxin production, treatment with antibiotics can do little to prevent a fatal outcome (6). Similar results were reported in animal models (7).…”
mentioning
confidence: 62%
“…Finally, massive edema and organ failure are produced as a consequence of toxin formation. Experience with the 2001 bioterrorism incident found that, once the disease reaches the phase during which patients show evidence of significant toxin production, treatment with antibiotics can do little to prevent a fatal outcome (6). Similar results were reported in animal models (7).…”
mentioning
confidence: 62%
“…Anthrax is one of the most extensively researched biological warfare agents (2)(3)(4)(5)(6). Nevertheless, important aspects of the disease remain poorly understood, in particular, the human response to low-dose exposure and the temporal progression of the disease, especially the dose dependence of the incubation period.…”
mentioning
confidence: 99%
“…5, page 2247). To investigate these issues, we formulated a mathematical model to compare several response strategies to a mass-casualty airborne anthrax attack in a large city.…”
mentioning
confidence: 99%